Carmustine-induced cardiotoxicity: A pharmacovigilance case report - Rodríguez-Tanta, Yesenia (2021)
Background: Carmustine is an alkylating agent used in the treatment of myeloma, lymphomas and other cancers. Cardiotoxicity due to carmustine is a rare adverse reaction that must be identified early to prevent fatal outcomes. Report case: We present an unusual case of acute cardiac toxicity related to the intravenous administration of carmustine. After stopping the carmustine, patient received symptomatic treatment and, finally was fully recovered. The case was reported as adverse drug reaction and we performed a pharmacovigilance causality assessment between carmustine and cardiotoxicity, resulting in probable (final score = 7). Conclusions: This case might be considered as a signal in pharmacovigilance. Clinicians should be aware of the potential risk of cardiotoxicity in patients exposed to carmustine. It is recommended to implement active pharmacovigilance to chemotherapy.